Kontrola obiegu dokumentów w organizacji gospodarczej - Iwasieczko, Beata (The Control of Accounting Document Circulation in Economic Entity, 2005)
In the article there has been an attempt to answer following questions: which feature of the ac-counting document are the most crucial in terms of economic entity management, is the control of accounting document circulation necessary? Since the accounting document beside the information, evidential function, they function as control function. This determine the necessity for the control of accounting circulation in economic entities - taking the peculiarity of the run business and companies needs in terms of management process into consideration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 22-25